Effect of maize plant population and nitrogen application on maize cassava intercrop - Kang, B.T.; Wilson, G.F. (1981)
The effects of varying the population density of maize cv. TZPB on the yields of maize and cassava grown in mixed stands with 10 000 cassava plants/ha were studied. Increasing the maize population from 10 000 to 30 000 plants/ha significantly increased the yield of maize grain but had no significant effect on the yield of cassava roots. The highest maize yield was given by a population of 70 000 plants/ha. The yield of cassava roots was significantly decreased by maize populations more than or equal to 40 000 plants/ha. The effects of 0, 60 or 120 kg N/ha on the yields of intercropped maize, cv. TZPB and TZE and cassava cv. TMS 30395 grown on freshly cleared Eupatorium fallow land were studied in 1978-80. In 1978-9 the yields from both cv. were not significantly affected by N, by increasing the maize population from 1 to 3 plants/hill or by intercropping with 10 000 cassava plants/ha. The cassava was harvested at 10 months after planting. The yield of roots decreased linearly with increasing N and was also reduced by intercropping with maize. In 1979-80 the yields of pure and intercropped maize were significantly increased by both rates of N. The cassava was harvested at 13 months after planting and the yield of roots was higher than in 1978-9 and was not affected by N or by intercropping with maize. At harvesting cassava plants grown in pure stands were vigorous and leafy and gave good visible response to N but those grown in mixed stands with maize were etiolated and had small foliage and poor branching. The land equivalent ratios for mixed maize + cassava crops were higher than for the corresponding pure crops.